A note on the representation for the Drazin inverse of 2 × 2 block matrices - Cvetković-Ilić, Dragana S. (Linear algebra and its applications, 2008)
In this note we consider representations of the Drazin inverse of 2 × 2 block matrices under conditions weaker than those used in recent papers on the subject, in particular in [D.S. Djordjević, P.S. Stanimirović, On the generalized Drazin inverse and generalized resolvent, Czechoslovak Math. J. 51 (126) (2001) 617–634; R. Hartwig, X. Li, Y. Wei, Representations for the Drazin inverse of 2 × 2 block matrix, SIAM J. Matrix Anal. Appl. 27 (2006) 757–771].